2021
DOI: 10.1590/1516-3180.2020.0738.r1.0402021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of unstable shoes on women with lumbopelvic postpartum pain: randomized clinical trial

Abstract: BACKGROUND: Back pain is a normal symptom during pregnancy and is expected to become worse beyond the first three months after childbirth. OBJECTIVES: To determine the effectiveness of wearing unstable shoes instead of conventional shoes, regarding pain intensity, low back mobility and stability, among women with lumbopelvic pain (LPP) during the postpartum period. DESIGN AND SETTING: Prospective, single-blinded, randomized clinical trial conducted at a podiatry and physiotherapy clinical center. METHODS: A ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…This phenomenon aligns with the findings of Yamamoto et al,20 who reported enhanced venous return to the leg through the use of heel-less shoes during walking at 80 m/min. This enhancement was attributed to increased recruitment of slow muscle fibers like the soleus muscle, paralleling the findings of our study wherein the unstable sole shoe activation prompted similar muscle activation 10. Unstable footwear has also been investigated in other contexts, such as addressing back pain 21…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This phenomenon aligns with the findings of Yamamoto et al,20 who reported enhanced venous return to the leg through the use of heel-less shoes during walking at 80 m/min. This enhancement was attributed to increased recruitment of slow muscle fibers like the soleus muscle, paralleling the findings of our study wherein the unstable sole shoe activation prompted similar muscle activation 10. Unstable footwear has also been investigated in other contexts, such as addressing back pain 21…”
Section: Discussionsupporting
confidence: 81%
“…This enhancement was attributed to increased recruitment of slow muscle fibers like the soleus muscle, paralleling the findings of our study wherein the unstable sole shoe activation prompted similar muscle activation. 10 Unstable footwear has also been investigated in other contexts, such as addressing back pain. 21 A systematic review in 2020 compared the influence of different footwear on the lower limb venous system, concluding that unstable shoes exhibited improved venous return parameters in contrast to regular footwear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations